Serotype distribution and clinical characteristics associated with streptococcus pneumoniae among Chinese children and adults with invasive pneumococcal disease: a multicenter observational study - Ma-Chao Li; Yao Wang; Hong Zhang; Yong Liu; Xue-Jun Chen; Hong-Wei Yang; Ping Ma; Ding-Cheng Wang; Bing-Chang Zhang; Ai-Ying Dong; Chun-Xin Wang; Yan Li; et al. (Taylor & Francis Group, 2021)
Few studies in China focused on serotypes of Streptococcus pneumoniae in patients with invasive pneumococcal disease (IPD). We aimed at investigating the serotype distribution for IPD-causing S. pneumoniae and vaccine coverage among Chinese children and adults. This was a multicenter, observational study to collect S. pneumoniae isolates from normal sterile sites and IPD-related clinical information among children and adults. Serotyping was performed by a Capsule-Quellung reaction test using type-specific antisera. The study collected a total of 300 eligible isolates (pediatric = 148, adult = 152) were serotyped in a central laboratory. The most prevalent serotypes were 19A (20.9%) and 23 F (20.3%) in the pediatric group; 3 (21.7%) and 19 F (11.8%) in the adult group. PCV10 had low-to-moderate serotype coverage rates for children (60.8%) and adults (34.2%). PCV13 and PPV23 had high coverage rates for children (89.9%, 93.2%) and adults (70.4%, 82.9%), respectively, Investigational PCVs including PCV15 and PCV20 had high estimated coverage rates in children (89.9%, 93.9%). The study identified 269 subjects with IPD reported as the primary diagnosis in the medical records. Sepsis (48/136, 35.3%) and pneumonia (48/133, 36.1%) had the highest occurrence in the pediatric and adult groups, respectively. Study findings showed that non-PCV7 S. pneumoniae 19A and 3 were the most prevalent serotypes in Chinese children and adults, respectively. High-valent vaccines had similar coverage rates and may have a greater potential in preventing IPD.